UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN (Studi Deskriptif di Sekolah Menengah Atas Islam Terpadu Mentari Ilmu Karawang) - Atik, Ayu Suci; Mansyur, Masykur H; Nurlaeli, Acep (Idaarah: Jurnal Manajemen Pendidikan, 2020)
The purpose of this research is to find out the efforts of the principal in improving the quality of education. This type of research uses descriptive qualitative methods. The subjects in this study were principals while the research informants were TU teachers and staff. Data collected in the form of observations, interviews, and documentation. Analyzed using data in the form of data collection, data reduction, data presentation, and drawing conclusions. The results of the principals’ research in improving the quality of education in SMAIT Mentari Ilmu through (1) Efforts are made to conduct routine programs in the form of habituation programs and flagship programs; (2) the implementation of the principal in the form of discipline, regular meetings, and rewarding; (3) overcoming consistent obstacles and implementing a determined policy, the solution is to improve the quality, innovate and support the skills of the learners.